Gambaran derajat stres pada pasien tumor payudara - Musani, Melda Ayu Amanda; Jaya, Muhammad Alim; Swarga, Tirta; Gani, Aziz Beru; Karsa, Nevi Sulvita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The diagnosis and treatment of breast cancer pose significant psychological challenges, often leading to stress that can negatively impact patients' quality of life and recovery. Purpose: To determine the level of stress in breast cancer patients. Method: This study used a descriptive design with a cross-sectional approach and a sample of 70 respondents. Data collection used the Depression Anxiety Stress Scale-42 (DASS-42) stress measurement instrument. The collected data were processed and analyzed univariately using Microsoft Excel to display the frequency distribution and percentage of each stress category. Results: The majority of respondents (89%) experienced stress, with severe stress being the highest (36%), followed by moderate stress (24%). The largest proportion of respondents were in the 41–50 age group (23%), and the most common type of tumor was right breast cancer (31%). High levels of stress are related to the psychological impact of the diagnosis, changes in body image, and anxiety about treatment, which are often exacerbated by the multidimensional life burdens of middle adulthood. Conclusion: Breast tumor patients experience a high prevalence of stress, with severe stress being the most prevalent. Suggestion: Holistic patient management is needed, integrating psychosocial interventions and medical therapy to improve overall patient well-being. Keywords: Breast Tumor;Right Breast Tumor; Stress Level. Pendahuluan: Diagnosis dan pengobatan tumor payudara menimbulkan tantangan psikologis yang signifikan, seringkali menyebabkan stres yang dapat berdampak negatif terhadap kualitas hidup dan proses pemulihan pasien. Tujuan: Untuk mengetahui gambaran derajat stres pada pasien tumor payudara. Metode: Penelitian ini menggunakan desain deskriptif dengan pendekatan cross-sectional dan sampel yang digunakan sejumlah 70 responden. Pengumpulan data menggunakan instrumen pengukuran stres Depression Anxiety Stress Scale-42 (DASS-42). Data yang terkumpul diolah dan dianalisis secara univariat menggunakan microsoft excel untuk menampilkan distribusi frekuensi dan persentase setiap kategori stres. Hasil: Menunjukkan bahwa sebagian besar responden (89%) mengalami stres, dengan kategori stres berat sebagai yang tertinggi (36%), diikuti stres sedang (24%). Proporsi terbesar responden berada pada kelompok usia 41–50 tahun (23%), dan jenis tumor yang paling sering ditemukan adalah Tumor Mamma Dextra (31%). Tingginya tingkat stres berkaitan dengan dampak psikologis dari diagnosis, perubahan citra tubuh, serta kecemasan terhadap pengobatan yang sering diperburuk oleh beban kehidupan multidimensi pada masa dewasa madya. Simpulan: Pasien tumor payudara mengalami prevalensi stres yang tinggi dengan kategori stres berat sebagai yang paling dominan. Saran: Diperlukan manajemen pasien secara holistik dengan mengintegrasikan intervensi psikososial dan terapi medis untuk meningkatkan kesejahteraan pasien secara menyeluruh. Kata Kunci: Derajat Stres; Tumor Mamma Dextra; Tumor Payudara.